pH-responsive graphene oxide loaded with targeted peptide and anticancer drug for OSCC therapy - Li, Ran; Gao, Ruifang; Zhao, Yingjiao; Zhang, Fang; Wang, Xiangyu; Li, Bing; Wang, Lu; Ma, Lixin; Du, Jie (Frontiers in Oncology, 2022)
Oral squamous cell carcinoma (OSCC) is the most common type of cancer occurring in the oral and maxillofacial region. Despite of the advances in the diagnosis and treatment, the overall 5-year survival rate remains about 40%-50% in the past decades. Various nanotechnology-based carrier systems have been investigated for their potentials in the OSCC treatment. However, because of the lack of active targeting of tumors, their application is limited. Studies have shown that gastrin releasing peptide receptors (GRPRs) are overexpressed on many human cancers, including head and neck squamous cell carcinoma. Herein, we aimed to develop a GRPR-targeted nano-graphene oxide (NGO) nanoprobe drug delivery system for OSCC therapy. DOX@NGO-BBN-AF750 was synthesized by non-covalent bonding method to couple carboxylated-NGO with BBN-AF750 (bombesin antagonist peptides conjugated to Alexa Fluor 750) and DOX (doxorubicin) through π-π and hydrogen bonding. Internalization and antitumor activities were carried out in human HSC-3 cancer cells. The tumor pH microenvironment was simulated to study the release of anti-tumor drug DOX from DOX@NGO-ant BBN-AF750 complex under different pH conditions. DOX@NGO-BBN-AF750 showed internalization into HSC-3 cells. The IC50 (50% inhibitory concentration) was 5 µg/mL for DOX@NGO-BBN-AF750 in HSC-3 cells. Furthermore, DOX@NGO-BBN-AF750 showed a pH-sensitive drug release rate, and a dose-dependent and pH-responsive cytotoxicity in HSC-3 cells. DOX@NGO-BBN-AF750 presents the characteristics ensuring a slow release of DOX from the nanoprobe, thereby protecting the drug from degradation and prolonging the half-life of the drug. This report provides a versatile strategy to achieving targeted and imaging-guided therapy of OSCC.